BACE1 Inhibitor Lanabecestat (AZD3293) in a Phase 1 Study of Healthy Japanese Subjects: Pharmacokinetics and Effects on Plasma and Cerebrospinal Fluid Aβ Peptides. (15th June 2017) - Sakamoto, Kei; Matsuki, Shunji; Matsuguma, Kyoko; Yoshihara, Tatsuya; Uchida, Naoki; Azuma, Fumihiko; Russell, Muir; Hughes, Glen; Haeberlein, Samantha Budd; Alexander, Robert C.; Eketjäll, Susanna; Kugler, Alan R.
Abstract: Lanabecestat (AZD3293; LY3314814) is an orally active potent inhibitor of human β‐secretase 1 in clinical development for the treatment of Alzheimer disease. In this first Japanese clinical study for an Alzheimer disease intervention to include cerebrospinal fluid (CSF) sampling in Japanese elderly healthy subjects, we report the pharmacokinetics and effects on plasma and CSF amyloid‐β (Aβ) peptides of lanabecestat in a phase 1 study involving 40 healthy Japanese subjects (NCT02005211). No safety and tolerability concerns were identified in healthy Japanese subjects exposed to lanabecestat up to the highest doses given, which is consistent with observations in a US phase 1 study of lanabecestat. Exposure to lanabecestat was similar for young and elderly subjects and increased in a dose‐dependent manner. For elderly subjects, plasma lanabecestat half‐life after multiple dosing was 12 to 17 hours (on days 10 and 14). Robust plasma and CSF Aβ peptide reductions were also seen at all doses, with CSF Aβ42 concentrations reduced by 63% and 79% in the 15‐ and 50‐mg lanabecestat groups, respectively. CSF soluble amyloid‐β precursor protein β also decreased following lanabecestat treatment. Suppression of CSF Aβ peptides was similar in elderly healthy Japanese subjects and US patients with mild to moderate Alzheimer disease. Lanabecestat is a promising potentially disease‐modifying treatment in phase 3 development for patients with early Alzheimer disease.